Determinan Kualitas Audit: Etika, Fee, dan Motivasi Auditor - Denny Kurnia; Annisa Rofiyanti (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
Audit quality is a central issue in public accounting because stakeholders rely on audit opinions to reduce information risk and to strengthen confidence in financial reporting. This study examines the effects of auditor ethics, audit fees, and auditor motivation on audit quality at KAP SH & Rekan. The research uses an associative quantitative design with a survey approach. Primary data were collected through questionnaires distributed to 33 auditors, and the sample was determined using saturated sampling. Data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing. The findings show that auditor ethics has a positive and significant effect on audit quality, audit fee has a positive and significant effect on audit quality, and auditor motivation has a positive and significant effect on audit quality. Simultaneous testing also confirms that the three variables jointly affect audit quality with an adjusted R square of 0.966. These results imply that audit quality is strengthened when auditors maintain ethical conduct, when audit fees support adequate audit procedures, and when motivation encourages professional responsibility.